Features of Surgical Treatment of Patients with Splenic Artery Aneurysms (Case Report and Literature Review) - Yuriy H. Orel; Hlib Y. Orel; Yuriy Z. Khorkavyi; Oleg M. Slabyy (Ukrainian Journal of Cardiovascular Surgery, 2022)
Despite the insigniϐicant prevalence, aneurysms of the splenicartery take a dominant share among all visceral aneurysms with a predominance of morbidity in women of childbearing age. Taking into account the mostly asymptomatic course and the high risk of mortality due to its rupture, timely diagnosis and correct treatment strategy remain extremely important. Questions regarding the choice of surgical treatment tactics for patients with this pathology remain debatable.The aim. Demonstration of a clinical case, improvement of diagnosis andsurgical treatment of patients with splenic artery aneurysms.Clinical case. Female patient G., 32 years old, with complaints of periodic pain in the left hypochondrium, signs of portal hypertension against the background of cavernous transformationof the portal vein, history of recurrent bleeding from the esophageal veins, hypersplenism admitted with a pre-diagnosed aneurysm of the splenic artery of giant dimensions (diameter 8x5 cm). The patient was qualified for open surgery and aneurysm resection with splenectomy and spleen autotransplantation by N. Roth. The postoperative period was complicated by the occurrence of reactive pancreatitis on day 7, which was successfully treated conservatively. In the future, the course was unremarkable. The remote follow-up lasted two years, and no recurrence of the aneurysm was detected. The performed immunogram showed normal results.Conclusion. The timely diagnosis makes it possible to establish the correct diagnosis, justify the treatment tactics and prevent fatal complications. Open surgical intervention in somecases remains the method of choice in the treatment of this pathology. Autotransplantation of the spleen has shown good long-term results and can be performed in patients of this category for the prevention of immunodeficiency states.